Preconditioning Calves Using Co-products - Matt Hersom; Todd Thrift; Joel Yelich (EDIS, 2011)
Preconditioning cattle is a way to add value to a calf crop. It involves weaning, vaccination, and acclimating cattle to eating from feed bunks. This publication will focus on the nutrition, feedstuff considerations, and performance potential for different co-product options in preconditioning management. This 10-page fact sheet was written by Matt Hersom, Todd Thrift, and Joel Yelich, and published by the UF Department of Animal Science, May 2011.